2011
DOI: 10.1089/ten.tea.2010.0496
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of Plasmid DNA Encoding Bone Morphogenetic Protein-2 with a Biodegradable Branched Polycationic Polymer in a Critical-Size Rat Cranial Defect Model

Abstract: This study investigated the delivery of plasmid DNA (pDNA) encoding bone morphogenetic protein-2 in the form of polyplexes with a biodegradable branched triacrylate/amine polycationic polymer (TAPP) that were complexed with gelatin microparticles (GMPs) loaded within a porous tissue engineering scaffold. More specifically, the study investigated the interplay between TAPP degradation, gelatin degradation, pDNA release, and bone formation in a critical-size rat cranial defect model. The pDNA release kinetics in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
30
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…This is in accordance with previous studies, in which scaffolds containing plasmid DNA did not result in enhanced bone formation [32,33]. The incorporation of TMC/pDNA-hBMP-2 complexes into PLGA/HA scaffolds also resulted in decreased bone formation compared with the delivery of recombinant BMP-2 protein with this system in our previous study (unpublished work).…”
Section: Discussionsupporting
confidence: 92%
“…This is in accordance with previous studies, in which scaffolds containing plasmid DNA did not result in enhanced bone formation [32,33]. The incorporation of TMC/pDNA-hBMP-2 complexes into PLGA/HA scaffolds also resulted in decreased bone formation compared with the delivery of recombinant BMP-2 protein with this system in our previous study (unpublished work).…”
Section: Discussionsupporting
confidence: 92%
“…[23][24][25][26][27] Meng et al have reported that bone tissue engineering requires endogenous bone cells, extracellular matrix, and scaffold materials to be addressed holistically as a three-component system. 28 Endogenous bone cells, which mainly differentiate from BMSCs, play an important role in bone formation.…”
Section: Discussionmentioning
confidence: 99%
“…Poly(propylene fumarate) (PPF), is a biodegradable fumarate-based synthetic polymer that has shown promise in craniofacial bone applications. [6][7][8][9][10] A PPF construct typically incorporates PPF, a crosslinking agent (N-vinyl pyrrolidone, NVP), a radical initiator (benzoyl peroxide, BP), and an accelerator (N,N-dimethyl-p-toluidine, DMT). PPF can crosslink in situ, thus providing the possibility of injecting the material directly into a fracture or bony defect.…”
Section: Introductionmentioning
confidence: 99%